Vitamin B12 (Cobalamin) and Micronutrient Fortification in Food Crops Using Nanoparticle Technology - Oh, Soojin; Cave, Gareth; Lu, Chungui (Frontiers in Plant Science, 2021)
It is necessary to develop a resilient food supply that will withstand unexpected future shocks and deliver the required amounts of nutrients to consumers. By increasing the sustainability of food and agriculture, the food system will be able to handle challenges such as climate change, declining agricultural resources, growing population/urbanisation, pandemics and recessions/shortages. Micronutrient deficiency, so called hidden hunger, is one of the major malnutrition consequences worldwide, particularly in middle- or low- income countries. Unlike essential mineral or nutrient compounds, micronutrients could be less of a priority due to their small amounts of requirement. However, insufficient micronutrients caused critical adverse health symptoms and it is excessively vital for young children development. Therefore, there have been numerous attempts to enhance minerals and nutrients in food crops, including biofortification, food fortification and supplementation. Based on several interventions involving micronutrients, modern technology, such as nanotechnology, can be applied to enhance sustainability and to reduce the food system’s environmental impact. Previous studies address various strategies or interventions to mitigate major micronutrient deficiency including iron, iodine, zinc and vitamin A. Comparably small amounts of studies address vitamin B12 deficiency and its fortification in the food crops. Vitamin B12 deficiency occurs along with other micronutrient deficiencies such as folate, iron and zinc worldwide particularly, in the middle- and low-income countries with serious adverse health effects including in the nervous or blood systems. Mitigation for B12 deficiency has mainly focused on developing pharmacological and medical treatments such as vitamin B12 serum or supplements. Further studies are required to undertake a sustainable approach to fortify Cbl in plant food for public health worldwide. This review paper highlights nanoparticle applications as a promising technology for enhancing vitamin B12 without conventional genetic modification requirements. The nanoparticle can efficiently deliver the mineral/nutrient using coating techniques to targeted sites into the plant. Vitamin B12 coated nanoparticles would be absorbed, translocated and accumulated by the plant and eventually enhance the bioavailability in food crops. Furthermore, by reducing adverse environmental effects, such as leaching issues that mainly occur with conventional fertiliser usage, it would be possible to develop more sustainable food fortification.